Nikša Bareza à la HBL: A biographical contribution behind the encyclopedic scenes - Karlo Radečić (Studia Lexicographica)
Based on the research of literature (mostly periodicals), archival material and other sources, as well as contacts with several European cultural institutions and knowledge of some of his interpretations of operatic and symphonic repertoires, this paper presents an original biobibliography of Nikša Bareza (1936–2022), one of the greatest Croatian conductors, in a form that follows the basic features of an article in the Croatian Biographical Dictionary (Hrvatski biografski leksikon, HBL) published by the Miroslav Krleža Institute of Lexicography in Zagreb (the structure of the text, a specific way of listing literature), but with various deviations from the nature of an encyclopedic text, such as exhaustiveness and, most obviously, the addition of a scientific apparatus (footnotes). This kind of biobibliography à la HBL, the only one besides that of historian and lexicographer Trpimir Macan written by Nikša Lučić in 2005, combines encyclopaedic lexicography with music historiography. The standard scientific apparatus that accompanies the biobibliography written in the specific encyclopaedic form at the same time partly demonstrates the »hidden work« invested in creating many of the articles written for the Croatian Biographical Dictionary and, implicitly, the methods, principles, and challenges of the critical writing of biographies within the context of encyclopaedistics in general. In this first extensive biobibliography of Bareza, his international and Croatian career are covered in detail, including all opera productions he conducted at Croatian theatres and festivals, as well as their reception (which includes excerpts from reviews of concert and operatic performances and other articles which cover him in some detail); a detailed original critical evaluation of his characteristics as a conductor is also given, and his place among Croatian reproductive musicians and his role in the musical scene of Croatia in the second half of the 20th century and in the 21st century are examined. An addendum listing Bareza’s opera repertoire is also presented.